Pemodelan Kerusakan Beton akibat Hujan Asam Menggunakan Software MATLAB - Ahmad, Irma Aswani; Pertiwi, Nurlita; Taufieq, Nur Anny S (Journal of Mathematics, Computations and Statistics, 2022)
Several cities in Indonesia experienced rain with acidity levels below the standard threshold. This condition illustrates that the rainwater is categorized as acid rain. Acid rain causes damage to crops, the aquatic environment, and human disease. This damage also occurred in construction buildings, causing porous concrete and reinforcement. This damage also occurs in construction buildings, causing the concrete and reinforcement to become porous, affecting the durability of the building. The purpose of this study is to predict the decrease in the durability of concrete buildings by making modeling using Matlab software. This research is experimental research with cylindrical and beam-shaped specimens. The variation used is a mixture of concrete using rice husk ash substituting 0%, 5%, and 10% by weight of cement. The tests carried out are compressive, flexural, and water absorption tests. This data was analyzed to form a durability model with the help of Matlab software. The results showed that the durability modeling was in the form of a hyperbolic paraboloidal with a second-order polynomial equation